Effects of budding time on success and sapling growth in almond on Erzincan conditions - Aslantas R.; Güleryüz M. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
The highest healing ratio of budding union was 100 per cent on 20 August while the lowest was 85.57 per cent on 5 September. Budding done on 20 August and 5 September started shoot growth (1.11 per cent) in the same vegetation period, but it was 4.44 per cent on 5 August and 37.74 per cent on 20 July buddings. Shoot length was between 1 cm and 13 cm. Also, gumming in the budding point was not observed on 20 August budding time but it occurred as 2.22 per cent on 5 August, 7.77 per cent on 5 September and 17.27 per cent on 20 July. Budding time was not significant for sapling development. While sapling diameter ranged between 14.68 mm (20 July) and 15.28 mm (5 August), their lengths between 152.25 cm (5 September) and 156.51 cm (5 August). The best time for T-budding in Erzincan conditions was 15-25 August.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)